Experimental and computational Fluid Dynamics study of separation gap effect on gas explosion mitigation for methane storage tanks - Li, Jingde; Hao, Hong; Shi, Y.; Fang, Q.; Li, Zhan; Chen, L. (Elsevier, 2018)
This paper presented both experimental and numerical assessments of separation gap effect on vented explosion pressure in and around the area of a tank group. A series of vented gas explosion layouts with different separation gaps between tanks were experimentally investigated. In order to qualitatively determine the relationship between the separation gap distance and explosion pressure, intensive computational Fluid Dynamics (CFD) simulations, verified with testing data, were conducted. Good agreement between CFD simulation results and experimental data was achieved. By using CFD simulation, more gas explosion cases were included to consider different gas cloud coverage scenarios. Separation gap effects on internal and external pressures at various locations were investigated.